Hemicellulose extraction and characterization of oil palm empty fruit bunches - Mohd Zaki, Nor Nadiha; Abdul Rahman, Russly; Bakar, Jamilah (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
In Malaysia, local production of oil palm produces huge amount of empty fruit bunches during oil processing. However, it is not fully utilized and cause a serious environmental issue because of the burning of this by-product. Thus, the study on utilization of this lignocellulosic biomass is important to improve their added value and subsequently decrease the agriculture waste. In general, oil palm empty fruit bunches consist of cellulose (30-40%), hemicellulose (20-30%) and lignin (10-20%). In this study, empty fruit bunches (EFB) have been treated with alkaline using 4% and 13% of sodium hydroxide in different ratio (1:10 to 1:50). The highest yield of hemicellulose (6.35%) was obtained from the treatment using 13% sodium hydroxide with 1:10 ratio. Proximate and chemical composition of oil palm empty fruit bunches also has been determined.